The Roman collegia : the modern evolution of an ancient concept - Perry, Jonathan Scott. (Mnemosyne, Supplements, 2006)
This volume maintains that contemporary events, ideologies, and institutions have shaped scholarly work on the ancient Roman collegia , a group of institutions known principally from epigraphic and legal sources. It traces the origins of thinking on the subject from the creation of the Corpus Inscriptionum Latinarum through the political and social movements of the 19th and 20th centuries in Western Europe. The bulk of the book focuses particularly on the intersection of scholarship and economic theory in Fascist Italy, as the collegia were analysed by the Istituto di Studi Romani, incorporated into the Mostra Augustea della Romanità , and ultimately championed by the Minister of National Education, Giuseppe Bottai, in 1939.